Place of the Supply Chain Strategy in an Integrated Business Management System - L.A. Plotnikova; N.V. Lopukhova (International Journal of Supply Chain Management, 2020)
Abstract— This article reveals the importance and role of supply chain strategy in creating an integrated business management system. The concept of an integrated business management system and the prerequisites for its creation in a modern company are revealed. The goals and objectives of the integrated business management system and its main elements are outlined. The main conclusion is that achieving the company's goals will be most effective through the implementation of an integrated business management system. The authors reveal the relationship of all elements of the integrated business management system with the elements of integrated reporting of the company, since an effective business management system should be aimed at meeting all the expectations of each of the interested users. The authors believe that among the elements of an integrated business management system, an internal supply chain strategy system and a risk management system find their significant place, information about which is reflected in the public reports of modern companies. In other words, supply chain strategy is an effective tool within the functioning of an integrated business management system. The authors believe that it is most effective to structure the supply chain strategy system in accordance with the company's business processes, since control procedures must be applied at each stage of the main activity. The functions of supply chain strategy, its elements and tools depending on business processes are revealed. The importance of regular monitoring of key performance indicators is emphasized, which is carried out within the framework of the General supply chain strategy system, which contributes to the normal and effective functioning of the integrated business management system in the company.